STRATEGI HARGA JUAL PRODUK KULINER MAKANAN PADA USAHA BAKSO PAKNO DI KOTA KENDARI - Majid, Retno Sefianty; Palilati, Alida; Yusuf, Yusuf; Ansir, Ansir; Hartini, Hartini (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2021)
One of the business world today which in great demand is from the restaurant business. Many businesses are trying to explore the restaurant business led to an increasing number of restaurant that also increasing competition among restaurants become extremely high, especially in Kendari City. In running the business as well as to be able to survive inte competitive world of business today, every business owner should be able to take the right decisions as the application of marketing strategy and in determining the price of selling.Â The purpose of this study was to determine how the selling price determination done by the pakno meatball restaurant,as well as to determine how the selling price determination on the theory of cost plus pricing method, and then compare the result of selling price determination done by the pakno meatball restaurant with the selling price determination based on the theory of cost plus pricing method.This research was a case study and in data gathering techniques used observation and interview methods. The result showed a different to the selling price which currently apply to the selling price is calculated by using the method of cost plus pricing. In which the given selling price of the Pakno Meatball restaurant is lower than the selling price that is calculate based on cost plus pricing method. So, setting the selling price should be done precisely because the price is too hight will make the product less competitive, while the sale price too low will lead to losses for the business.